Bottleneck Phenomena and Cyclical Change: The Role of the Iron and Steel Industry - Broude, Henry W. (Quarterly Journal of Economics, 1954)
I. Introduction, 437. — II. Possible leverage role of the steel industry, 439. — III. Bottleneck phenomena, 448. — IV. Bottlenecks and formulation of counter-cyclical policy, 456.